Strategic Human Resource Planning in the Era of Digital Transformation - Adiazmil. S., Aan; Hidayat, Muhammad; Basuil, Dynah A. (Penelitian dan Pengembangan Ilmu, 2024)
Digital transformation has had a significant impact on business and human resource management (HR). This research explores